Setting the stage for autonomous cars: a pilot study of future autonomous driving experiences. Issue 7 (1st September 2015) - Pettersson, Ingrid; Karlsson, I.C. MariAnne
Abstract : Autonomous cars are undergoing rapid development. In order to gain acceptance and adoption, there is a need to understand how users will respond to the technology, and what possible benefits or difficulties they perceive. A prerequisite for eliciting this information is the involvement of users. Having said that, several studies have demonstrated the problems associated with investigating 'the future'. In a pilot study, two different qualitative approaches for exploring users' expectations for future automotive technology were applied in two studies. The first study encompassed drawing, collaging and interviewing while the second study used drawing and enactment of expected use to mediate a shift from today to tomorrow. A content analysis revealed that the first study provided information on social implications, trust and every‐day activities in autonomous cars, whereas the second study provided further in‐depth details about the interaction and interior design expectations, as well as trust and anticipated activities. The results contribute to the author's knowledge on how different studies of the same topic can elicit different types of data.